2019
DOI: 10.1016/j.aott.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after ACL reconstruction with free quadriceps tendon autograft versus hamstring tendons autograft. A retrospective study with a minimal follow-up two years

Abstract: Objective The aim of this retrospective study was to compare the clinical outcomes of anatomic single bundle ACL reconstruction using either a free quadriceps tendon autograft or a quadrupled hamstring autograft with a minimum follow-up of 24 months. Methods Consecutive patients undergoing ACL reconstruction using either a free quadriceps tendon autograft or hamstring tendon autograft from January 2013 to December 2014 were included. ACL reconstruction was done in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Another cohort study that compared the use of QT autograft versus HT autograft in a retrospective review of 48 patients with a minimum follow-up of 2 years reported significantly improved manual laxity test results in both groups after surgery; the IKDC score and Tegner activity score were better and not significantly different between the groups, the anatomical ACL reconstruction with QT showed knee stability and functional outcome scores similar to those of HT autografts, but the patients with QT autograft showed better flexor muscle strength recovery 19 . In another retrospective study of 72 patients with a follow-up of 24 months, similar clinical results both autografts were found 20 . In our study, in the evaluation of the Lysholm score and IKDC Subjective Knee Evaluation Form results, all patients showed better results during the follow-up and at the end of the evaluation, with no significant differences between groups.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Another cohort study that compared the use of QT autograft versus HT autograft in a retrospective review of 48 patients with a minimum follow-up of 2 years reported significantly improved manual laxity test results in both groups after surgery; the IKDC score and Tegner activity score were better and not significantly different between the groups, the anatomical ACL reconstruction with QT showed knee stability and functional outcome scores similar to those of HT autografts, but the patients with QT autograft showed better flexor muscle strength recovery 19 . In another retrospective study of 72 patients with a follow-up of 24 months, similar clinical results both autografts were found 20 . In our study, in the evaluation of the Lysholm score and IKDC Subjective Knee Evaluation Form results, all patients showed better results during the follow-up and at the end of the evaluation, with no significant differences between groups.…”
Section: Discussionsupporting
confidence: 62%
“…There were some limitations in our study, including the reduced sample size and relatively short follow-up. One of the strengths of our study is that unlike previous studies on this topic that used a retrospective cohort study design [18][19][20] , this was a randomized controlled clinical trial. In terms of the level of clinical evidence, the preferred design for a clinical trial is often a randomized controlled trial; prospective and retrospective cohort studies are ranked lower because of the biases inherent to their design.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, just one study, done in Romania, by Todor et al (2019), compared the clinical outcomes of these two distinct autografts [ 13 ]. Todor et al study's primary findings indicated that comparable results in terms of stability and patient-reported outcomes could be reached using either a HAM or a free QUADRI autograft [ 13 ]. They revealed no statistically significant differences between groups in terms of instrumented laxity tests, Lysholm scores, and modified Cincinnati scores.…”
Section: Discussionmentioning
confidence: 99%
“…It is the main stabilizer against anterior tibial translation, with functional importance in sports. The aforementioned outcome measures apply also in cruciate ligament reconstruction [2,3,17]. We deliberately excluded ACL surgeries to maintain group homogeneity and target the non-acute pain, meniscus and early degeneration subpopulation.…”
Section: Discussionmentioning
confidence: 99%